DEMOGRAPHIC AND CLINICAL-EPIDEMIOLOGICAL PROFILE OF PATIENTS WITH SURGICAL SITE INFECTION - Gomes Campos, Regina Kelly Guimarães (2024)
To evaluate the clinical, epidemiological and demographic profile of patients with surgical site infection.  A documentary study with 55 sheets of notification of hospital-acquired infections of a referral hospital located in the city of Quixadá, in the months of January and February 2018. The demographic profile showed that the majority of people notified by IRAS was a woman; between 19 and 59 years of age; and was admitted to the accommodation; for less than three days. Clinical-epidemiological profile showed that most patients had performed Cesarean delivery; with length greater than or equal to 40 minutes; and the surgery was classified as clean; and the surgical site infection more common was the superficial. Practically, it is not conducting routine culture collection, according to the body of the suspect site infection. The clinical outcome of patients notified shows that almost all have evolved to improve/discharge. We need improvements in the work environment of the hospital services for professionals can play a quality and safety assistance.